Praktik Pembuatan Ekoenzim dalam Upaya Menstimulus Pengetahuan dan Peduli Lingkungan pada Siswa SMP: Practice of Making Ecosenzymes In an Effort to Stimulate Environmental Knowledge and Care for Students of SMP - Karyadi, Bhakti; Ruyani, Aceng; Mayub, Afrizal; Parlindungan, Deni; Prayogo, Bambang (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
This community service aims to equip students and teachers of SMP IT Khoiru Ummah Rejang Lebong with knowledge about managing school gardens using household waste through ecoenzymes, natural boosters, and POC. This school has a large area of underutilized land, especially for organic waste management. Household waste is not managed correctly, and most of it is disposed of in landfills, even though it can be processed into valuable products. Converting organic waste into eco-enzymes is expected to reduce waste and create a greener, more environmentally friendly school ecosystem. This training was carried out from April to December 2024, by using the Participatory Action Research (PAR) method, divided into three stages: exploration, provision of materials and practice, and evaluation. The evaluation's student response data show that around 61% of students demonstrated excellent knowledge, 30% good, and 9% sufficient. The level of concern for the environment was very high. The success of this activity was measured by the level of participation and enthusiasm among participants, which reflected the objectives of community service: increasing awareness and skills in waste management. Further evaluation is needed to assess the long-term impacts and to determine how this activity can be implemented outside of school, thereby providing benefits to the surrounding community.